2012
DOI: 10.1001/archneurol.2011.802
|View full text |Cite
|
Sign up to set email alerts
|

Partial Trisomy 4q Associated With Young-Onset Dopa-Responsive Parkinsonism

Abstract: To describe a patient who developed a youngonset, dopa-responsive parkinsonism linked to a de novo heterozygous interstitial duplication 4q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Secondly, we also hypothesised that, above a certain duplication length threshold, the individual will exhibit a more complex phenotype with features unusual for SNCA multiplications. Consequently, two individuals with such complex presentations, one described by Garraux et al (2012) 11 and the case reported herein carrying duplications larger than 5Mb were excluded from this analysis. Published individuals were also excluded if any of the following were true: a) there was no information on the length of the duplication, b) there was insufficient clinical information, c) clinical presentation was clearly inconsistent with parkinsonism, d) they were affected relatives of probands with SNCA duplications but their carrier status wasn’t assessed (efigure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, we also hypothesised that, above a certain duplication length threshold, the individual will exhibit a more complex phenotype with features unusual for SNCA multiplications. Consequently, two individuals with such complex presentations, one described by Garraux et al (2012) 11 and the case reported herein carrying duplications larger than 5Mb were excluded from this analysis. Published individuals were also excluded if any of the following were true: a) there was no information on the length of the duplication, b) there was insufficient clinical information, c) clinical presentation was clearly inconsistent with parkinsonism, d) they were affected relatives of probands with SNCA duplications but their carrier status wasn’t assessed (efigure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analyses have revealed widely variable sizes of the duplicated genomic region, ranging from 0.2 to 41.2 Mb and containing anywhere from 2 to 150 genes [1113]. Combined with haplotype analyses, this data indicates there is no common ancestor but duplications have arisen independently in most of the families reported [12].…”
Section: Review Of Snca Duplication Casesmentioning
confidence: 99%
“…There are reports of two patients whose parents were healthy and were not carriers of SNCA duplication. Thus these two patients had a de novo mutation [13, 14]. There is no clear correlation between the size of the duplication and resulting clinical phenotypes, implying that other genetic and environmental factors may contribute.…”
Section: Review Of Snca Duplication Casesmentioning
confidence: 99%
“…The largest multiplication detected so far is about 41.2 Mb, containing 150 genes and defined a partial trisomy 4q [55]. The smallest one sizes about 0.2 Mb and was found in a Japanese family [43].…”
Section: Sncamentioning
confidence: 96%
“…Their clinical course was similar to typical sporadic PD without severe progression or cognitive decline. Other cases of sporadic PD carrying de novo SNCA duplication were later revealed by different detection assays [55][56][57][58][59].…”
Section: Sncamentioning
confidence: 99%